Rice Bran Stabilization And G-Oryzanol Content Of Two Local Paddy Varieties Ir 64 And Cisadane Muncul - Evy Damayanthi (Jurnal Teknologi dan Industri Pangan, 2001)
An autoclaving procedure was developed to produce stable rice bran from two local paddy varieties IR 64 and Cisadane Muncul. The stable rice bran showed no significant increase in free fatty acid content for 144 hours at 37oC. In the optimum wet heating process, rice bran was heated at 121oC and held for 3 minutes before cooling for both varieties. Stable rice bran contained 3.8 % moisture and the content of total tocopherol was not much changed by heating process, i.e., 209.8 mg/100 g rice bran oil and 279.8 for control (without heating process) of IR 64 variety and 227.4 mg/100 g rice bran oil and 248.8 for control of Cisadane Muncul variety, respectively. The content of g-oryzanol varied and was depended on the degree of milling ranged from 39.1 to 147.7 mg/100 g rice bran oil for both of IR 64 and Cisadane Muncul rice varieties. The content of soluble dietary fiber varied and was depended on the degree of milling which ranged from 3.56 to 8.76 % for both of IR 64 and Cisadane Muncul rice varieties. The content of insoluble dietary fiber varied and was depended on the degree of milling which ranged from 15.00 to 25.38 % for both of IR 64 and Cisadane Muncul rice varieties. Keywords : rice bran, autoclave, stabilization, g-oryzanol, total tocopherol, dietary fiber.